أثر توزع النباتات و الرش بحمض الهيوميك على بعض الصفات الإنتاجية للحلبة (L. (Trigonella foenum- graceumالمزروعة في بساتين الحمضيات - عبد العزيز محمد; أشرم مازن; حربا رحاب (Latakia University Journal -Biological Sciences Series, 2018)
نفذ البحث خلال الموسم الزراعي 2017 ، في حقل الزراعة العضوية - قسم بحوث الحمضيات التابع لمركز البحوث العلمية الزراعية في طرطوس، بهدف دراسة أثر توزع نباتات الحلبة والرش بحمض الهيوميك في بعض الصفات الإنتاجية لنبات الحلبةا لمزروعة في بساتين الحمضيات. زرعت النباتات في الجور في ثلاث كثافات نباتية هي : نبات واحد في الجورة ، نباتين في الجورة ، ثلاث نباتات في الجورة ، وأربع تراكيز من حمض الهيوميك هي : شاهد بدون رش،100 ملغ/ل ، 200ملغ/ل ،300ملغ/ل . صممت التجربة بطريقة تصميم القطاعات العشوائية الكاملة بنظام القطع المنشقة لمرة واحدة Split plot desigon . إذ شكل عدد النباتات بالجورة القطع الرئيسية و الرش بالحمض العضوي الهيوميك القطع المنشقة، بثلاث مكررات لكل معاملة . بينت النتائج الآتي: تفوق توزع النباتات (ثلاث نباتات في الجورة) بفروق معنوية على( نباتين ، ونبات واحد في الجورة الواحدة ) من حيث ارتفاع النبات و إنتاجية الهكتار . تفوق توزع النباتات (نبات واحد في الجورة ) بفروق معنوية على (نباتين في الجورة , ثلاث نباتات في الجورة ) من حيث عدد الأفرع /النبات ،عدد الأزهار /النبات،إنتاجية النبات من البذور . تفوق الرش بحمض الهيوميك باستخدام تركيز 300 ملغ/ل بفروق معنوية على الرش بالتركيزين 200 ملغ/ل ،100 ملغ/ل ، وعلى الشاهد بدون رش في مؤشرات ارتفاع النبات ، عدد الأفرع ،عدد القرون ،عدد الأزهار ، إنتاجية النبات من البذور، إنتاجية الهكتار من البذور تفوق التداخل بين ( 3 نباتات في الجورة X تركيز الرش 300 ملغ/ل ) على باقي التداخلات في التجربة من حيث ارتفاع النبات و إنتاجية الهكتار من البذور . تفوق التداخل بين (نبات واحد في الجورة X تركيز الرش 300 ملغ /ل ) على باقي التداخلات في التجربة من حيث عدد الأفرع/النبات، عدد الأزهار /النبات ،إنتاجية النبات من البذور . The research was carried out during the agricultural season 2017, in the field of organic agriculture - the Citrus Research Department of the Center for Agricultural Scientific Research in Tartous, to study the effect of the distribution of Fenugreek plants and spraying with humic acid in growth and productivity characteristics of the plant. Use three plant densities: one plant per hal, two plants per hal, three plants per hal, and four concentrations of humic acid: without spraying, 100 mg / L, 200 mg / L, 300 mg / L. The experiment was designed according to the design of the complete random Blocks in the form of splitting plot desigon. The number of plants per hall formed the main plots and spray with organic acid formed spilt plots. The results showed the following • The distribution of plants (three plants per hal) was significantly higher to (two plants per hal and one per hal) in plant height and productivity per hectare • The plant density (one plant per hall) was significantly superior to (two plants per hal, three plants per hal) in number of branches / plants, number of flowers / plants, plant productivity of seeds. • Spraying of humic acid with a concentration of 300 mg / L was significantly superior to the concentrations of( 200 mg / L, 100 mg / L, without spraying ) at plant height, number of branches, number of pods, number of flowers, plant productivity of seed , hectar productivity of seed • The Interaction between (3 plants in Al-Joura X and 300 mg / l) exceeded the restof the experiment in terms of plant height and productivity per hectare. • The Interaction between (one plant in al-Joura X and the concentration of spraying 300 mg / l) exceeded the other experiment interventions in terms of number of branches / plants, number of flowers / plants, plant productivity of seeds.